Barriers to Evidence-Based Decision Making in Public Health: A National Survey of Chronic Disease Practitioners - Jacobs, Julie A. (Association of Schools of Public Health, 2010)
OBJECTIVE: Existing knowledge of evidence-based chronic disease prevention is not systematically disseminated or applied. This study investigated state and territorial chronic disease practitioners' self-reported barriers to evidence-based decision making (EBDM). METHODS: In a nationwide survey, participants indicated the extent to which they agreed with statements reflecting four personal and five organizational barriers to EBDM. Responses were measured on a Likert scale from 0 to 10, with higher scores indicating a larger barrier to EBDM. We analyzed mean levels of barriers and calculated adjusted odds ratios for barriers that were considered modifiable through interventions. RESULTS: Overall, survey participants (n=447) reported higher scores for organizational barriers than for personal barriers. The largest reported barriers to EBDM were lack of incentives/rewards, inadequate funding, a perception of state legislators not supporting evidence-based interventions and policies, and feeling the need to be an expert on many issues. In adjusted models, women were more likely to report a lack of skills in developing evidence-based programs and in communicating with policy makers. Participants with a bachelor's degree as their highest degree were more likely than those with public health master's degrees to report lacking skills in developing evidence-based programs. Men, specialists, and individuals with doctoral degrees were all more likely to feel the need to be an expert on many issues to effectively make evidence-based decisions. CONCLUSIONS: Approaches must be developed to address organizational barriers to EBDM. Focused skills development is needed to address personal barriers, particularly for chronic disease practitioners without graduate-level training.